1991
DOI: 10.1111/j.1440-1819.1991.tb02523.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Clonazepam on Rolandic Discharge of Benign Epilepsy of Children with Centro‐Temporal EEG Foci

Abstract: Summary 1) CZP had marked effects on RD. RD disappeared in 8 (73%) of 11 patients treated with CZP alone and 6 (43%) of 14 treated with CZP in combination with other drugs. Even when RD persisted, its amplitude and frequency decreased in some patients. 2) In the group treated with CZP in combination with other drugs, RD disappeared in all 5 patients with the persistent RD, of whom 2 had arachnoid cyst. Of the 6 patients with frequent seizures, 2 were subsequently diagnosed as having CPS and SPS, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…In contrast, the autonomic manifestations in PS are postulated to arise from the involvement of the amygdale region or other emetic centers immediately spreading from the occipital focus [8,20] . Frequent attacks resistant to medication and a prolonged seizure period were characteristic of early-onset BECT, as described in previous reports [9,18,30,31] . In contrast, PS patients had shorter active seizure periods and less frequent seizures, while the incidence of status epilepticus was higher, accounting for 75 % in PS as compared to 9.7 % in early-onset BECT.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In contrast, the autonomic manifestations in PS are postulated to arise from the involvement of the amygdale region or other emetic centers immediately spreading from the occipital focus [8,20] . Frequent attacks resistant to medication and a prolonged seizure period were characteristic of early-onset BECT, as described in previous reports [9,18,30,31] . In contrast, PS patients had shorter active seizure periods and less frequent seizures, while the incidence of status epilepticus was higher, accounting for 75 % in PS as compared to 9.7 % in early-onset BECT.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we focused on early-onset BECT, which was described before the concept of PS was proposed. Children with early-onset BECT have a few different clinical features from those with typical BECT, being characterized by an earlier onset of epilepsy, frequent seizures, longer active seizure periods, and greater resistance to antiepileptic drugs [1,9,18,30,31] . Loiseau et al reported that patients with an onset under 4 years of age had longer active seizure periods than those with a later onset age based on a long-term follow-up study of 168 children with BECT.…”
Section: Discussionmentioning
confidence: 99%
“…If one alleges the hypothesis of adverse effects caused by interictal changes (3,4), a drug treatment should not only control seizures, but should preferably also improve the EEG. Besides seizure control, only two drugs, clonazepam (CZP) and STM, are reported to have positive effects on the EEG in BECTS (7,8). In a trial comparing CZP, valproate (VPA), and carbamazepine (CBZ) in BECTS (7), global EEG normalization after 4 weeks was observed in 15 of 20 patients treated with CZP and in one of 10 patients receiving VPA.…”
Section: Discussionmentioning
confidence: 99%
“…If interictal epileptiform discharges are a possible contributing factor to poor neuropsychological performance in this cohort, 6,8 a drug treatment should not only control seizures, but should preferably also improve the EEG. As well as seizure control, clonazepam (CZP) and STM are reported to have positive effects on the EEG in patients with BECTS 2,5,9,10 . In a trial comparing CZP, valproate (VPA), and carbamazepine (CBZ) in patients with BECTS, global EEG normalization after 4 weeks was observed in 15 of 20 patients treated with CZP, and in one of 10 patients receiving VPA 9 .…”
Section: Discussionmentioning
confidence: 99%